STEPWISE THERAPY OF CHRONIC ADENOIDITIS - Андриянова, Ирина Владимировна; Ильенкова, Наталья Анатольевна; Вахрушев, Сергей Геннадиевич (Mother and Baby in Kuzbass, 2023)
The article provides a review of the literature, considered the heterogeneity of chronic adenoiditis and approaches to treatment based on the allocation of clinical manifestations of various phenotypes, biological and genetic markers and endotypes, taking into account the etiology and pathophysiology of the disease. Selection of phenotypes and endotypes contributes to a better understanding of the essence of the disease and is advisable for developing an individual approach to therapy, since some variants of chronic adenoiditis and pharyngeal tonsil hypertrophy may be characterized by resistance to standard therapy. The article formulates theoretical prerequisites for changing the paradigm of treatment of chronic adenoiditis from anti-infective and/or anti-allergic to step therapy, depending on the response to the initial treatment.